Restablecimiento automático ante fallas del suministro de energía eléctrica en un alimentador primario de la red de distribución de la Empresa Eléctrica Riobamba S.A. - Quisimalín Villacís, Leonardo David (2023)
One of the global goals of distribution systems is to meet the demand in line with demographic growth. This has led to the search for new real-time technologies to monitor, analyze and process information to generate automated distribution. This paper seeks a methodology for automation of a feeder of the distribution system, with the use of devices and technologies responsible for real-time decision making for the operation of the distribution system, therefore, the objective of this paper is to minimize outage times of electricity supply, which are impacted in the quality of service to final customers. In this sense, the methodology tries to identify a permanent fault, isolate the fault section and reconfigure the feeder to restore the power supply automatically to the final customers, using information from intelligent tele-commanded devices in the feeder topology. Maintaining the power supply and having a high level of reliability is the main interest for the final customers of the power distribution companies. Several transfer options are presented in the result of the present investigation, which describe automated reconfiguration scenarios by sectioning the faulted section and maintaining or restoring power supply to the non-faulted sections. Automated reconfiguration of the network causes the feeder to self-recover, which maintains power supply to most consumers by automatically rerouting one or more sections out of fault. Automatic power supply automation will indicate the point of failure to the control center operators in seconds, for faster corrective actions can be taken more quickly and resources can be reduced, without neglecting the economic gain of energy at the moment of restoring power supply to the non-failed sections.